Meanwhile In Malmö: Exploring temporary urbanism - Westberg,Frida (2026)
Temporary urbanism has emerged as a prominent field in urban planning and research,encompassing a wide range of terms such as meanwhile use, tactical urbanism, and DIY.Despite its growing relevance as a more sustainable and flexible approach to traditionalplanning, the concept remains ambiguous. Several scholars describe the field of temporaryurbanism as disorganized, confusing, and difficult to define. This study examines howtemporary urbanism is conceptualised and applied in practice, with a particular focus onhow underlying power relations shape its outcomes. It is based on a comparative casestudy of two ongoing projects in Malmö: Färjeterminalen in Nyhamnen and Backa Kåken in Kirseberg. Adopting a qualitative research approach, the study combines semi-structuredinterviews and document analysis to explore how temporary use is framed, structured, andgoverned by different actors. The analysis is informed by critical urban theory, drawingprimarily on Lefebvre’s perspective of the production of space and the right to the city.Findings demonstrate that temporariness is not the defining feature of temporary urbanism.Instead, important aspects are ownership, control over development, and the capacity totransform temporary use into lasting spatial rights. While Färjeterminalen represents amunicipally driven, strategic use of temporariness to facilitate long-term development,Backa Kåken exemplifies a bottom-up initiative seeking to challenge existing ownershipstructures and retain value locally. The study shows that temporary urbanism can serveboth as a tool for urban development and as a means of contesting dominant planningpractices. However, it also highlights that temporary interventions are not inherentlysustainable and inclusive, but depend on the institutional and economic conditions in whichthey are embedded. Temporary use is not even inherently time-limited, but is often intendedto result in long-term change.
Keywords: Temporary urbanism; Governance; Spatial production; Urban transformation; Malmö